Rapidly progressing primary splenic angiosarcoma with fatal hemorrhagic event. (August 2014) - Cho, Eun Ae; Choi, Won-Young; Kim, Seung-Hun; Hong, Ji-Yun; Jung, Sung-Hoon; Kim, Min-Jee; Hwang, Jun-Eul; Bae, Woo-Kyun; Shim, Hyun-Jeong; Lee, Kyung-Hwa; Cho, Sang-Hee; Chung, Ik-Joo
Abstract : Primary angiosarcoma of the spleen is an extremely rare malignancy. Splenic angiosarcoma is difficult to diagnose, and treatment is often challenging. The prognosis is dismal, with a mean survival of less than 1 year. Currently, no standard treatment methods have been established. Anecdotal reports suggest that early diagnosis and prompt splenectomy followed by cytotoxic chemotherapy can be effective treatment modalities. We report a case of rapidly progressing primary splenic angiosarcoma with multiple liver and bone metastases and a fatal hemorrhagic outcome.